Cardiometabolic, Dietary and Physical Health in Graduate Paramedics during the First 12-Months of Practice – A Longitudinal Study. (21st June 2022) - Meadley, Ben; Wolkow, Alexander P.; Smith, Karen; Perraton, Luke; Bowles, Kelly-Ann; Bonham, Maxine P.
Abstract: Objective: Shift work is an established risk factor for poor health yet is necessary for paramedics to provide continuous care to the public. It is unknown how early into a career shift work may begin to impact health. This study sought to identify changes in cardiometabolic health, diet, aerobic capacity, physical activity and health-related quality of life (HRQoL) in graduate paramedics during the first 12-months of their career. Methods: Fifty-six paramedics with no history of regular shift work (28 female, 28 male; median age 24.5, IQR 23-26 years) were recruited for this study. Dietary patterns (food frequency questionnaires) and HRQoL (36-Item Short Form Questionnaire) were assessed at baseline, 6- and 12-months. Body weight, body mass index (BMI) and blood samples (fasting lipids, glucose, insulin and C-reactive protein) were measured at baseline and 12-months to ascertain cardiometabolic health risk. A subset of participants (n = 19; 10 female, 9 male) wore a physical activity monitor for 12 months and completed baseline and 12-month maximal aerobic capacity assessments (V̇O2max ). Results: Body weight and BMI decreased in males and increased in females (-0.7% versus 1.7%, p = 0.02). HRQoL and dietary intake did not change over 12-months, except for a small decrease in fat intake (−1%). Consumption of core/healthy foods was lower than recommended at all timepoints. Biomarkers of cardiometabolic health were within normal range and did not change over 12-months, excepting insulin where a small non-significant increase was seen (+0.5 mIU/L, p = 0.61). Baseline V̇O2max was 41.4 (37.1-49.1) ml.kg −1 .min −1, with no change noted at 12-months. Comparison of quarterly physical activity data showed no difference in steps per day (p = 0.47) or moderate to vigorous physical activity (MVPA, p = 0.92) across the 12-months. Paramedics completed less MVPA on day shifts compared to rostered days off (−14.68 minutes, p = 0.04). Conclusions: Dietary patterns, HRQoL, cardiometabolic health, aerobic capacity and physical activity levels did not change meaningfully in the first year of practice. Some dietary behaviors and physical activity levels could be improved and may mitigate health effects of exposure to shift work. Long-term follow-up of this group may aid in developing programs to enhance health for paramedics and other health workers.